Model Of The Russian Crypto Currency Exchange Market - AleÑ…androvich Galanov, Vladimir; Grigorievich Perepelitsa, Denis; Vladimirovna Galanova, AleÑ…andra; Fedorovna Chelukhina, Natalia; Ahmetshaevna Asyaeva, Elmira (International Journal of Engineering and Technology, 2018)
In recent years, a new market trading in cryptocurrencies and instruments based on them has been formed. Its participants who are interested in it according to the rules they develop create the market of cryptocurrencies. The goal of this article is to substantiate the possibility of a more organized market of cryptocurrencies with its legitimate exchange market in its top with two possible versions: a) as a specific exchange market consisting of an exchange center and decentralized markets (exchanges) of certain cryptocurrencies and b) as a market of cryptocurrencies built in into certain segments of the already existing exchange markets. Functional aspects of creating the cryptoinstrumentsâ€™ exchange market are considered, and possible models of organizing it are offered. The authors are based on the need to strengthen the regulatory participation of the state during the formation of this market because such participation allows better observance of public interests under the conditions when the private interest is a driving force of the market. The state regulation somehow minimizes financial risks for ordinary participants of the cryptocurrenciesâ€™ market, but at the same time limits the impact of the new market towards possible destabilizing effects on the monetary circulation in the country and on the current investment processes in it.Â